2018
DOI: 10.29333/ejmste/90088
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Watching Authentic English Videos with and without Subtitles on Listening and Reading Skills of EFL Learners

Abstract: Watching English videos can be considered as a powerful and popular tool with regard to learning English as a foreign language, and ought to be devoted serious attention by teachers and researchers. The present study attempts to explore the potential effects of watching authentic English videos (movies, TV shows, etc.) with subtitles (English and Slovak) and without subtitles on listening and reading skills. A total of thirty Slovak university EFL learners were divided into three groups according to their view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 24 publications
(21 reference statements)
4
20
1
Order By: Relevance
“…The results revealed that the effects of watching captioned on the video are stronger on acquiring vocabulary and enhancing language proficiency than on content comprehension. Another supported findings by Faraco & Muntane (2016) and Metruk (2018) that subtitles in the origin language (L1) can be used to retune the link of speech-sounds with perceptive categories, then the intermediate to advanced English learners can adapt to English sounds in a more efficient fashion. Watching authentic English vides represents a powerful and popular tool when it comes to learning languages, and ought to to be devoted considerable attention by teachers and researchers.…”
Section: Introductionsupporting
confidence: 61%
“…The results revealed that the effects of watching captioned on the video are stronger on acquiring vocabulary and enhancing language proficiency than on content comprehension. Another supported findings by Faraco & Muntane (2016) and Metruk (2018) that subtitles in the origin language (L1) can be used to retune the link of speech-sounds with perceptive categories, then the intermediate to advanced English learners can adapt to English sounds in a more efficient fashion. Watching authentic English vides represents a powerful and popular tool when it comes to learning languages, and ought to to be devoted considerable attention by teachers and researchers.…”
Section: Introductionsupporting
confidence: 61%
“…So, following Talavan (2007a) the visual dimension, is a significant feature of the authentic videos since it makes the understanding process easier thanks to the gestures and the context in which the situation is taking place. That is why most of the examples given when talking about authentic videos are movies, tv shows, series, and so on (Weyers, 1999;Metruk, 2018;Kim, 2015). In this way, video becomes a "multi-sensory medium" (Swaffar & Vlatten, 1997).…”
Section: Authentic Videomentioning
confidence: 99%
“…In addition, there is a bunch of studies that assure that authentic videos result in such a good strategy to be used in the foreign language classroom since it allows the student to feel more engaged and focused as well as an arise in the student's motivation (Bacon and Finneman, 1990;Weyers, 1999;Block, 1993;Kim, 2015;Metruk, 2018). Video-based instruction improves aspects of learners' oral production too, particularly their "confidence in speech" (Weyers, 1999).…”
Section: Authentic Videomentioning
confidence: 99%
“…The use of such tools as courses of leading educational organizations, hosted on specialized platforms, as part of the implementation of project activities, can be an effective way to solve this problem. We put the importance of such courses under investigation, primarily due to their relevant authentic video materials as a worldly recognized means of increasing motivation and the development of listening comprehension skills (Baeva, 2017;Kim, 2015;Metruk, 2018). Below we consider the main characteristics of some popular educational platforms, as well as the advantages of each one of these resources.…”
Section: Problem Statementmentioning
confidence: 99%